THE IMPORTANCE OF ORGANIZATIONAL PSYCHOLOGY WITHIN INSTITUTIONS - Silva, Fernanda Camila Bragantin da; Rodolpho, Daniela (Revista Interface Tecnológica, 2025)
Organizational Psychology is a field of psychology that focuses on the study of human behavior in the context of organizations, such as companies, government institutions, NGOs and other entities. Its main objective is to understand the psychological processes that occur within these organizations and apply this knowledge to improve the performance, efficiency and well-being of the individuals and groups that work in them. Organizational Psychology is an essential field for understanding the complex world of contemporary organizations. This article explores the fundamental pillars of this discipline, focusing on the history of Organizational Psychology, the impact of organizational climate and culture, and team performance. The objective of the work was to present a literature review on organizational psychology, showing that this field of psychology plays a fundamental role in understanding and improving human dynamics, diversity and inclusion, mental health at work, balance between personal and professional life, ethical leadership, conflict resolution and adaptation to new ways of working within modern organizations.